A new Indian record and morphological variation for Eulimnadia khoratensis Rogers et al., 2016 (Crustacea: Branchiopoda: Spinicaudata) - Padhye, Sameer M.; Kulkarni, Mihir R. (Zootaxa, 2017)
Eulimnadia Packard, 1874 is the most species rich and widely distributed genus within the Limnadiidae (Reed et al. 2015). Species identification relies primarily on egg morphology as adult morphological characters show high variability, sometimes within the same populations and hence of little use (Rabet, 2010; Rogers et al. 2012). Seven species are currently known from the Indian subcontinent (sensu Rogers & Padhye 2015) and SE Asia (Rogers et al. 2016). Of these, four species, viz. E. compressa (Baird, 1860), E. michaeli Nayar & Nair, 1968 and E. indocylindrova Durga Prasad and Simhachalam, 2004, E. azisi Babu and Nandan, 2010 are known from peninsular India (Padhye et al. 2015; Rogers & Padhye, 2015), although, much of this region remains unstudied (Padhye pers. obs.). With this background, we present a new Indian record of E. khoratensis Rogers, Dadseepai and Sanoamuang, 2016 from the Western region of Maharashtra state, India, extending its distribution a few thousand kilometers westwards.